Vers une compréhension bio-psycho-sociale du développement de la maladie coronarienne et de son évolution suite à l’infarctus - Dumont, Serge; Deshaiest, Gilles; Dubé, Clémence (Canadian Journal of Counselling and Psychotherapy, 2008)
This paper addresses the topic of coronary disease. The first section presents and discusses the body of knowledge available in the literature of the past few decades. From the multi-factorial view of past empirical research, it goes forward in proposing the development of a bio-psycho-social view of the coronary disease. While it recognizes the essential contribution of empirical research and the medical sciences to the understanding of this prevailing sickness in contemporary life, it suggests to call for the collaboration of the human and social sciences. Some new research avenues are presented and the role of qualitative research methods is briefly discussed.